Conversion of Biomass to Organic Acids by Liquefaction Reactions Under Subcritical Conditions - Yüksel Özşen, Aslı (Frontiers in Chemistry, 2020)
The point of this research paper is to assess the impacts of different reaction parameters on cellulose conversion as the principle segment of lignocellulosic biomasses for the production of value-added chemicals, particularly levulinic acid. Hazelnut shell waste was chosen as model biomass since hazelnut is a standout amongst the most cultivated agricultural crops in Turkey. Besides, Turkey provide 70% of the world's total hazelnut production. It was found that when the reaction temperature, time and acid concentration were 280 °C, 120 min and 50 Mm, levulinic acid yield and conversion of hazelnut shell were found as 13.05% and 65.40%, respectively. Addition of H2SO4 enhanced the production of levulinic acid from waste hazelnut shell. Another method which is hybrid process could be used to produce value-added chemicals from lignocellulosic biomass. Hybrid process basically combines hydrolysis and electrolysis in subcritical water. It was claimed that if constant current was applied to the reaction medium through specially designed electrodes in subcritical water environment, electrolysis could alter the hydrolysis reaction of cellulose in a way of protonation of intra-and inter-molecular hydrogen bonding around anode and as a result electrolysis in subcritical water could decrease necessary thermal energy to hydrolyze the β(1-4) glycosidic linkage. Therefore, we developed a green hybrid process by combining hydrolysis and electrolysis in subcritical water without using any toxic, organic solvents and catalyst. Effects of especially applied current and temperature on the product distribution and conversions of cellulose were revealed and hydrothermal electrolysis reaction pathway of cellulose was proposed. The significance of the interaction indicated that, applied voltage had major impact on cellulose hydrolysis. Maximum cellulose conversion (82%) was achieved at 230 oC and 180 minutes of reaction time in 25 mM of H2SO4. Application of 8.0 V of applied voltage to the reaction medium at reaction temperature of 230 ºC increased the TOC conversion (50.3%) with acid concentration of 25 mM in comparison with current-free experiments. Thus, the idea of electrochemically generated acid layer due to the dissociation of water around anode is supported.